Persuading Me to Eat Healthy: A Content Analysis of YouTube Public Service Announcements Grounded in the Health Belief Model. Issue 1 (1st January 2017) - Zhang, Xueying; Baker, Kim; Pember, Sarah; Bissell, Kim
ABSTRACT: The current study presents a content analysis of public service announcements (PSAs) promoting healthy-eating behavior on YouTube. A total of 341 PSAs within a one-year period were retrieved and analyzed based on the Health Belief Model (HBM). The results demonstrated that a variety of sources attempt to educate the public about eating healthy but differ in what they choose to emphasize. All the four elements drawn from the HBM model were present in PSAs but not equally. The use of persuasive message appeals appeared to be matched with content elements. The most viewed, liked, and commented PSAs are also examined. Implications are provided for conducting theory-based content analysis and social media public campaigns in designing healthy-eating PSAs.